Methodology for Automated Hardening of GNU/Linux System Configurations based on Results of Security Scans: A Conceptual Review - Maciej WALCZAK (Communications of International Proceedings, 2021)
This article proposes a methodology for automated hardening of GNU/Linux system configurations. It allows to improve the system’s security level while minimising the impact on the availability of provided services. Correlated results of security scanners were used for the preparation of appropriate recommendations.
Keywords: Hardening; GNU/Linux Operating System; Security Scan.